BUTERFLI D3.19 Report - Kim, Jung-Hoon; Forte, Maxime; Choi, Kwing-So (2017)
D3.19 Report on the experimental results on transition delay in the “Juju” TRIN1 wind tunnel by the VR DBD actuators based on wall-normal jets